Inflammasome regulation and activation in the intestinal epithelium - Lei, A (2017)
Microbiota colonisation of the intestinal tract makes it difficult for pattern recognition receptors (PRR) to discriminate between beneficial microbes and harmful pathogens. We aim to define the roles of cytosolic Nod-like receptors (NLR) in intestinal immunity and homeostasis. Upon activation, some NLR form inflammasomes that mediate the release of inflammatory cytokines and pyroptosis, an inflammatory form of cell death. NLR activation in the non-hematopoietic compartment was shown to be protective during acute intestinal infection. To identify the cell type responsible for this protection, we generated transgenic mice in which the key inflammasome adaptor molecule Asc is selectively ablated in intestinal epithelial cells (IEC) (AscΔVC) and observed that inflammasomes are important for controlling Citrobacter rodentium clearance in these mice. To further dissect the importance of pathogen clearance by IEC inflammasome, ex vivo cultures of primary IEC organoids were established. Thus far this system has revealed profound differences in inflammasome regulation between IEC organoids and bone marrow-derived macrophages (BMDM). This research will inform our understanding of cell type-specific regulation of inflammasomes.